Effects of selective logging on the mating system and pollen dispersal of Hymenaea courbaril L. (Leguminosae) in the Eastern Brazilian Amazon as revealed by microsatellite analysis - Carneiro, F. S. [UNESP]; Lacerda, A. E. B.; Lemes, M. R.; Gribel, R.; Kanashiro, M.; Wadt, L. H. O.; Sebbenn, A. M. (Elsevier B.V., 2011)
Using nine microsatellite loci, we studied the effects of selective logging on genetic diversity, mating system and pollen dispersal in a population of the tree species Hymenaea courbaril, located in a 546 ha plot in the Tapajos National Forest, Pars State, Brazil. We analyzed 250 offspring (nursery reared seedlings) collected after a logging episode from 14 open-pollinated seed trees. These were compared to 367 seedlings from 20 open-pollinated seed trees previously collected from the pre-logging primary forest. The genetic diversity was significantly lower in the post-logging seed cohort. In contrast to the pre-logging population, significant levels of selfing were detected in the post-logging population (t(m), = 0.962, P < 0.05). However, correlated matings were reduced and the effective number of pollen donors almost doubled after harvesting (3.8 against 7.2). Logging also reduced pollen immigration into the plot (from 55% to 38%) and we found no significant correlation between the size of the pollen donors and the number of seeds fathered. Inside the plot, pollen dispersal distance was shorter before logging than after (827 and 952 m, respectively) and the reproductive pollination neighbor area (A(ep)) was larger (average of 178 ha). The individual and average variance effective population size within families (ranged from 1.80 to 3.21, average of 2.47) was lower than expected in panmictic populations (N-e = 4). The results indicate that while logging greatly reduced the levels of genetic diversity after logging, it also increased genetic recombination within the population and constrained crossing among related individuals. The results show that low-density tropical tree species such as H. courbaril, when harvested in moderate levels may be resilient to a reduction in the reproductive population and may maintain similar levels of outcrossing and pollen dispersal after logging. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gene flow; Jatoba; Pollen dispersal; Reduced impact logging; SSR loci; Tropical trees